MANAJEMEN KERJASAMA DALAM MENINGKATKAN MINAT BAKAT SISWA DI MAN 1 BANDAR LAMPUNG - Paramitha, Fannysa; Romlah; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of collaborative management in supporting the development of student interests and talents through extracurricular activities at Islamic schools (madrasahs). Extracurricular activities not only serve as a means of developing non-academic skills but also serve as a medium for character development, responsibility, discipline, and social skills in students. The implementation of extracurricular activities requires planned, organized, and sustainable management to optimally achieve the goal of developing student potential. MAN 1 and MAN 2 Bandar Lampung are Islamic schools that actively develop extracurricular programs through collaboration between student affairs, mentors, administrators, and students. This study aims to analyze the planning, organization, implementation, and supervision of collaborative management programs to enhance student interests and talents at MAN 1 and MAN 2 Bandar Lampung.This study used a qualitative approach with field research. Data collection techniques were conducted through interviews, observation, and documentation. The research informants consisted of the vice principal for student affairs, extracurricular teachers, and other stakeholders involved in the implementation of extracurricular activities at MAN 1 and MAN 2 Bandar Lampung. Data analysis techniques were carried out through the stages of data reduction, data presentation, and conclusion drawing. Data validity was achieved through triangulation of sources and techniques to ensure the data obtained corresponded to conditions in the field.The results of the study indicate that collaborative management in developing student interests and talents at MAN 1 and MAN 2 Bandar Lampung has been implemented through structured management functions including planning, organizing, implementing, and monitoring. Program planning was carried out through coordination meetings and identification of student interests. Organization was carried out through the establishment of an extracurricular organizational structure and a clear division of tasks. Activity implementation was supported through active communication, assignment of tasks according to student abilities, and the provision of motivation and appreciation to students. Supervision was carried out through regular evaluation of student participation, activity quality, and the results of extracurricular program implementation. This research implies the importance of strengthening a participatory, collaborative extracurricular management system to support the development of student potential, character, and social skills in the madrasah environment.